Welcome To Dark Eden






[ New messages · Members · Forum rules · Search · RSS ]
Page 1 of 11
Forum moderator: FallenMoogla, Viper2550, Kira 
Forum » Welcome » General Disscusion » ZOMG MATH (tutor problems)
ZOMG MATH
FallenMooglaDate: Saturday, 2011-04-02, 5:01 PM | Message # 1
The Dark Lord
Group: Administrators
Messages: 66
Awards: 0
Reputation: 2
Status: Offline
3m^2+m-2=0
3m^2+m=2
m^2+(1/3)m=2/3
m^2+(1/3)m+(1/(2*3))^2=(2/3)+(1/(2*3))^2
m^2+(1/3)m+(1/6)^2=(2/3)+(1/6)^2
(m+(1/6))^2 =(24/36)+(1/36)
(m+(1/6))^2 =(25/36)
m+(1/6)=+-sqrt(25/36)
m+(1/6)=+-(5/6)
m= 1/6 + 5/6 or m= 1/6 - 5/6
{1,-4/6)
{1, -2/3}

2x^2-9x=-9
2x^2-9x=-9
x^2-9/2x=-9/2
x^2 - 9/2x + (-9/4)^2 = -9/2 + (-9/4)^2
x^2 - 9/2x + (81/4) = -9/2 + (81/4)
x^2 - 9/2x + (81/4) = 63/4
(x - (9/4))^2 = 63/4
x - 9/4 = +-sqrt(63/4)
X = -9/4 + sqrt(63/4) OR X = -9/4 - sqrt(63/4)

Correct?


 
Forum » Welcome » General Disscusion » ZOMG MATH (tutor problems)
Page 1 of 11
Search: